Hierarchical Porous Graphene Bubbles as Host Materials for Advanced Lithium Sulfur Battery Cathode - Han, Wenjie; Li, Qing; Zhu, Hua; Luo, Dan; Qin, Xianying; Li, Baohua (Frontiers in Chemistry, 2021)
The serious shuttle effect, low conductivity, and large volume expansion have been regarded as persistent obstacles for lithium sulfur (Li-S) batteries in its practical application. Carbon materials such as graphene are considered as promising cathode hosts to alleviate those critical defects and be possibly coupled with other reinforcement methods to further improve the battery performance. However, the open structure of graphene and the weak interaction with sulfur-species restrict its further development for hosting sulfur. Here in, a rational geometrical design of hierarchical porous graphene-like bubble (PGB) as a cathode host of Li-S system prepared by employing MgO nanoparticles as templates for carbonization, KOH as activation agent, and car tal pitch as a carbon source. The synthesized PGB owns a very thin carbon layer around 5 nm which can be comparable to graphite nanosheets. Its high content of mesoporous and interconnected curved structure can effectively entrap sulfur species and impose restrictions on their diffusion and shuttle effect, leading to a much stable electrochemical performance. The reversible capacity of PGB@S under 0.3 C still can be maintained at 831 mAh g-1 after 100 cycles and 512 mAh g-1 after 500 cycles.